2016
DOI: 10.1177/1753425916677073
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation leads to immune modulation and improved survival in a juvenile model of murine sepsis

Abstract: Children with severe sepsis are known to have altered zinc homeostasis and decreased circulating zinc levels, suggesting a role for zinc supplementation to improve outcomes. We tested the hypothesis that zinc supplementation would improve survival in a juvenile model of polymicrobial sepsis. Juvenile (13-14-d-old) C57BL/6 mice were treated with 10 mg/kg of zinc via i.p. injections (or vehicle) for 3 d prior to induction of polymicrobial sepsis via i.p. cecal slurry injections. Survival after sepsis was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In human sepsis patients and in animal models, low zinc levels (probably due to internal redistribution of zinc) are associated with increased sensitivity to sepsis and fatality to infection (112), thus it is proposed that zinc supplementation might be a treatment option to improve the outcomes of sepsis. In some studies to address this issue, increasing blood zinc levels has been shown to be protective in animal sepsis models (113, 114), which is to certain degree echoed by a limited number of clinical trials, mainly in neonates (115, 116). However, no consensus is reached at present because the benefit of zinc supplementation in sepsis cannot be confirmed in other studies (62, 117).…”
Section: Modulation Of Immune Function By Nutrients and Food Componentsmentioning
confidence: 99%
“…In human sepsis patients and in animal models, low zinc levels (probably due to internal redistribution of zinc) are associated with increased sensitivity to sepsis and fatality to infection (112), thus it is proposed that zinc supplementation might be a treatment option to improve the outcomes of sepsis. In some studies to address this issue, increasing blood zinc levels has been shown to be protective in animal sepsis models (113, 114), which is to certain degree echoed by a limited number of clinical trials, mainly in neonates (115, 116). However, no consensus is reached at present because the benefit of zinc supplementation in sepsis cannot be confirmed in other studies (62, 117).…”
Section: Modulation Of Immune Function By Nutrients and Food Componentsmentioning
confidence: 99%
“…As one example, exposure to organic dust increased lung damage, inflammation and macrophage hyper-activation in animals with zinc deficiency, predisposing these animals to pulmonary fibrosis, while zinc supplementation 24 h before induction of acute lung injury significantly attenuated the inflammatory reaction and tissue damage ( 17 , 67 ). Regarding systemic inflammatory diseases the number of studies showing benefits of especially preventive zinc supplementation is constantly increasing ( 17 , 18 , 58 , 65 , 68 ). Amongst the underlying mechanism, zinc's role as second messenger and importance in regulating intracellular signaling as detailed in Figure 1 were described as well as zinc's effects on the epigenome ( 56 , 57 , 69 – 74 ).…”
Section: Zinc Balances the Immune Response During Infectious Diseasesmentioning
confidence: 99%
“…The published animal studies mostly examined the effects of prophylactic zinc supplementation ( Table 2 ). In several of them the supplementation of zinc prior to induction of sepsis showed beneficial effects, such as improved survival, lower serum concentrations of pro-inflammatory cytokines, lower bacterial burden or improved pulmonary function compared to the control-group [ 50 , 83 , 84 , 85 ]. However, for the animal studies the results are also not consistent and a missing effect of zinc supplementation is reported [ 86 ] as well as a harmful outcome in a case where zinc was applied during the acute phase [ 87 ].…”
Section: Zinc Supplementationmentioning
confidence: 99%